Adverse drug reactions: analysis of spontaneous reporting system in Europe in 2007-2009 - Srba, Jindrich; Deščíková, Veronika; Vlcek, Jiri (European journal of clinical pharmacology, 2012)
PURPOSE: Spontaneous reporting systems in European countries are crucial for collecting adverse drug reaction (ADR) reports. The aim of this study was to evaluate reporting activity among countries and their strategy to increase the number of reports. We also established the best measure for assessment quantity of reports. METHODS: This was a retrospective observational study based on questionnaires and annual reports. The most reliable measure of reporting was determined by Spearman correlation coefficients. RESULTS: Data collected in spontaneous reporting systems in 26 European countries were analysed. In 2007, 2008 and 2009, the average value of reports per year per million inhabitants based on the safety databases of countries was 208, 236, 286, respectively; in comparison, that of Eudra- Vigilance was 311, 453 and 435, respectively. Twelve countries reached a significant level for signal detection of ADRs in 2009. The population-based reporting ratio (PBRR) was correlated to the total expenditure on health (ρ=0.499, p=0.023, n=21), public expenditure on health (ρ=0.477, p=0.035, n=20), density of physicians (ρ=0.336, p=0.136, n=21) and expenditure on pharmaceuticals (ρ=0.365, p=0.114, n=20). Strategies of regulatory authorities to increase reporting were determined. CONCLUSIONS: The results of this study make several noteworthy contributions regarding national spontaneous reporting systems. The relevance of the PBRR for the measurement reporting activity is clearly supported by the current findings. This study also shows that there is a general trend towards increased reporting activity. This is maintained by regional centres and encouragement of reporting. A further study would be helpful to assess the effectiveness of reporting systems at both the national and European level.
Keywords: Patient Participation; Data Collection; zapojení pacienta; farmakovigilance; Evropa; Pharmacovigilance; Europe; sběr dat; Databases, Factual; systémy pro sběr zpráv o nežádoucích účincích léků; Adverse Drug Reaction Reporting Systems; databáze faktografické